2012
DOI: 10.24908/ijsle.v7i1.4238
|View full text |Cite
|
Sign up to set email alerts
|

Formal Service Learning Opportunities: Engineering Internships in Social Entrepreneurship Organizations

Abstract: -Over the past three years, a collaboration between the School of Engineering andComputer Science and the Global Center for Social Entrepreneurship at the University of the Pacific has provided students with internship opportunities at five different social entrepreneurship organizations distributed among six countries. The summer internship program administered by the Global Center seeks to provide an enriching experience for participants, to raise awareness of the broad application of social entrepreneurship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies concurred that communication skills (oral and written) represented a highly important competency for engineers' professional practice [33][34][35]. However, while internship experiences generally contributed to the enhancement of the interpersonal and oral communication skills of engineering students [36,37], their contributions to writing skills were less obvious [31,32,38,39]. In a study that probed senior engineering students' knowledge about design processes, Bailey found that industrial experience made a positive difference to learning in only one knowledge areadocumentation [40].…”
Section: Theme 1 (Regarding the Learning Outcomes) Co-ops And Internmentioning
confidence: 99%
“…Studies concurred that communication skills (oral and written) represented a highly important competency for engineers' professional practice [33][34][35]. However, while internship experiences generally contributed to the enhancement of the interpersonal and oral communication skills of engineering students [36,37], their contributions to writing skills were less obvious [31,32,38,39]. In a study that probed senior engineering students' knowledge about design processes, Bailey found that industrial experience made a positive difference to learning in only one knowledge areadocumentation [40].…”
Section: Theme 1 (Regarding the Learning Outcomes) Co-ops And Internmentioning
confidence: 99%